An Investigation into Threshold Selection Methodologies for Spectrum Sensing Techniques in Cooperative Cognitive Radio Networks - Tanga, Champa; Kunya, Tage (International Journal of Computer Sciences and Engineering, 2024)
This study investigate the optimal conditions for variable SNR values and appropriate threshold values can be examined through concurrent analysis of Pf and Pm when employing energy detector techniques for spectrum sensing. As the proposed method demonstrates higher Pm and lower Pm at low SNR, it fulfills the EDSS optimality criteria for low SNR environments. Additionally, this approach enables threshold verification at high SNR values, and subsequent research could focus on primary user detection. Furthermore, diverse sensing techniques can be applied to contemporary wireless technologies. Additional investigation of various parameters utilizing different methodologies is strongly recommended to improve spectrum sensing outcomes in cognitive radio networks.